CTAB DNA extraction method optimization for quantification of lard content in cheese and butter using real-time PCR - Mohamad, N. A.; Mokhtar, N. F. Khairil; Rosman, N. N.; Mustafa, S. (Taylor and Francis, 2024)
Porcine adulteration in dairy products for economic purposes has been tackled mostly by protein- and lipid-based porcine detection methods. In this study, a DNA-based approach was used to determine the presence of porcine DNA in dairy products, especially butter and cheese. DNA was extracted by optimizing the conventional CTAB extraction method followed by an assessment of DNA fragmentation by real-time PCR assays targeting different sizes of amplicon. Butter and cheese DNA samples were analyzed using both endogenous and porcine-specific real-time PCR assays and the lard content was estimated based on the linear regression analysis of a series of different percentages of lard-adulterated butter and cheese DNA samples. Even though the optimization steps did not improve the DNA yield, the successful amplification of the 200 bp amplicon depicted high DNA quality. Approximately 1% lard was able to be quantified exhibiting high potential of the assay in quantifying porcine content in lard-adulterated highly processed food products.